New Frontiers in Artificial Intelligence JSAI-isAI 2011 Workshops, LENLS, JURISIN, ALSIP, MiMI, Takamatsu, Japan, December 1-2, 2011. Revised Selected Papers - Okumura, Manabu; Bekki, Daisuke; Satoh, Ken (Lecture Notes in Artificial Intelligence,, 2012)
This book constitutes the thoroughly refereed post-proceedings of four workshops held as satellite events of the JSAI International Symposia on Artificial Intelligence 2011, in Takamatsu, Japan, in December 2011. The 25 revised full papers presented were carefully reviewed and selected from numerous papers. The papers are organized in four sections according to the four workshops: Logic and Engineering of Natural Language Semantics (LENLS), Juris-Informatics (JURISIN), Algorithms for Large-Scale Information Processing in Knowledge Discovery (ALSIP), and Multimodality in Multispace Interaction (MiMI).